(untitled) (Gragoatá, 2021)
The rise of dystopian fiction in the past forty years is revealing of sociopolitical anxieties of the present, many of which can be interpreted as consequences of a capitalist form of organization. Through those narratives, literature has the power to make explicit such tensions, especially those now brought together by the contemporary perception of the Capitalocene. The objective of this paper, thus, is twofold: to discuss the possibilities of acknowledging dystopian fiction as an autonomous genre, and to examine how it exposes the ever-dynamic machinations of capitalism. To that end, several examples from modern and contemporary dystopian novels in English are presented and discussed.